KARAKTERISASI BAHAN FERROELEKTRIK BARIUM STRONTIUM TITANAT (Ba0.3 Sr 0.7TiO3) DENGAN MENGGUNAKAN DIFRAKSI SINAR-X (XRD) - Rahmad Efendi; Rahmi Dewi; Krisman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ferroelectric materials of  Barium Strontium Titanate  (BST) with its  composition  of Ba0,3Sr0,7TiO3  was  succesfully deposited by a solid solution method. The samples were prepared in the form of pellets  and then  were annealed  at  the temperature of 600, 700, 800oC.   Characteritation of the samples was performed  using X-Ray diffraction (XRD). The results of characteritation using XRD was described on a graph  of the intensity  vs. 2 theta. The XRD  patterns of  Ba0,3Sr0,7TiO3  have  peaks. It was confirmed that the material of Ba0,3Sr0,7TiO3 has cubic crystalline structure, and its lattice parameter was  in average of 3,961 Å. The particle sizes (D) and lattice strains (η) of the material that was annealed at temperature of 600, 700, 800°C for 1 hour were 42.60, 44.43, 46.89 nm and -4,49x 10-3, -4,05 x 10-3,  -2,96 x 10-3, respectively. The increase in annealed temperature will raise the particle size and lattice strain.